The Etiquette Reflected in Jane Austen's Works - Dewi, Anindya Nurul Kusuma; , Dr. Muhammad Thoyibi, M.S; , Dr. Phil. Dewi Candraningrum, M.Ed (2016)
Etiquette in England is interesting to analyze, because England has several periods and different manners along with the country development. One of them is Regency period. It had some manners that reflected in Jane Austen's novels. This research aims to identify types of etiquettes in the Jane Austen's novels; describe the etiquettes that reflected in the Jane Austen's novels; and reveal the underlying reason why Jane Austen addressed the etiquettes in the novels. This study is qualitative research which the researcher uses narrative research to analyze the works besides books and other related references to support the subject matter. The data of the research are the etiquette in the Jane Austen's novels: Sense and Sensibility (1811), Pride and Prejudice (1813), Mansfield Park (1814), Emma (1815), Northanger Abbey (1818), and Persuasion (1818) novels. The technique of data collection is done through documentation of library research. After all data have been collected, the researcher analyzed the data by using descriptive analysis. Based on the analysis there are five etiquettes in the six Jane Austen's novels, visiting manners, speaking manners, party and balls, dressing manners, and table manners. The etiquettes described through the conversations, author's narration, and character's behavior. The etiquettes were important for social interaction. The social rules applied for both ladies and gentlemen, and touched upon almost every area of daily life.